Triisopropylsilylacetylene-functionalised anthracene-alt-benzothiadiazole copolymers for application in bulk heterojunction solar cells. Issue 123 (25th November 2015) - Cartwright, Luke; Taylor, Lois. J.; Yi, Hunan; Iraqi, Ahmed; Zhang, Yiwei; Scarratt, Nicholas. W.; Wang, Tao; Lidzey, David. G.
Abstract : Triisopropylsilylacetylene-functionalised anthracene-based donor–acceptor polymers are presented along with their optical, electrochemical and photovoltaic properties in bulk heterojunction solar cells. Abstract : Three triisopropylsilylacetylene-functionalised anthracene (TIPSAnt) based polymers were synthesised by copolymerising TIPSAnt with either dithienyl-5, 6-difluoro-benzo[ c ]-[1, 2, 5]thiadiazole, dithienyl-benzo[ c ]-[1, 2, 5]thiadiazole or dibithiophenyl-benzo[ c ]-[1, 2, 5]thiadiazole to yieldPTATffBT, PTATBT-8 andPTAT2BT-8, respectively.PTAT2BT-8 demonstrated a reduced optical and electrochemical band gap, relative toPTATffBT andPTATBT-8 . The HOMO level ofPTAT2BT-8 (−5.32 eV) is significantly shallower compared to its counterparts. This can be attributed to increased intramolecular charge transfer along the polymer backbone; a consequence of the incorporation of additional thiophene spacer units. The photovoltaic properties of the polymers were investigated by fabricating bulk heterojunction (BHJ) polymer solar cells using PC70 BM as the electron acceptor.PTATffBT displayed limited solubility in common organic solvents and could not be used for the fabrication of photovoltaic cells. Optimised photovoltaic devices fabricated fromPTATBT-8 andPTAT2BT-8 demonstrated power conversion efficiencies of 2.36% and 3.15%, respectively.PTAT2BT-8 provided better efficiencies chiefly as a result of better J sc and FF values.